Sosialisasi Penggunaan Aplikasi Padlet sebagai Alat Informasi untuk Masyarakat Sadar Sehat - Andriani, Ririn; Rizqiyah, Rini; Rostiana, Lola (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
The aim of this activity is to disseminate information about Acute Respiratory Infections (ARI) using the Padlet application. The result of the activities that have been carried out is to explain how this idea works as optimally as possible, so that partner problems can be resolved. The following is an explanation or strategic steps, including: 1) the first step, namely the team first explains the program provided in the form of a Padlet application, in this case the team also explains how to use the application or provides a tutorial. Since the team has provided a Padlet account and has filled it with various information about Acute Respiratory Tract Infections (ARI), and this is also used as a solution to partner problems, partners just need to update, add, or edit again according to their wishes according to the problem. partners who need to be resolved; 2) second step, after the first step is completed, partners work together with local communities and youth to discuss and ask for opinions to further refine the content of the padlet so that when it is ready to be given to all village communities, they can understand and accept it well so that the problems experienced by them partners or the community can be resolved immediately; 3) the third step, after discussing the improvement of the contents of the padlet, the partners then announced that they would invite and ask for cooperation from the community to take part in socialization about Acute Respiratory Infection (ARI), also in Salindu Village, Southeast Pamona District, Poso Regency, socialization is often held for society; 4) the fourth step, where padlet is ready to be used and given to the community when socialization begins or is in progress, and partners begin to explain introducing the padlet application, how to use it, advantages and disadvantages, as well as a solution for alleviating hoaxes that are widespread in the community regarding infectious diseases Acute Respiratory Tract (ARI); and 5) the final step is that partners wait and respond and discuss online regarding community reviews of the padlet contents.